2022
DOI: 10.1101/2022.04.06.487357
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Drug combination prioritization for cancer treatment using single-cell RNA-seq based transfer learning

Abstract: Precision oncology seeks to match patients to the optimal pharmacological regimen; yet, due to tumor heterogeneity, this is challenging. Numerous studies have been conducted to produce clinically relevant pharmacological response forecasts by integrating modern machine learning algorithms and several data types. Insufficient patient numbers and lack of knowledge of the molecular targets for each drug under study limit their use. As a proof of concept, we use single-cell RNA-seq based transfer learning to conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…For example, we have already shown that we can use breast cancer cell lines for automatic cancer subtype classification starting from the single-cell transcriptomic dataset of patient biopsies ( 7 ). Recently, it has also been shown that with transfer learning, we can use the knowledge of sensitive drugs for each cell line to predict the patient's treatment once the patient’s cells were confidently mapped on the reference atlas ( 78 ). Here, we demonstrated our method has high accuracy in cell mapping even when we profile cells’ transcriptomes after several culture passages in a different batch or with a different sequencing technique.…”
Section: Discussionmentioning
confidence: 99%
“…For example, we have already shown that we can use breast cancer cell lines for automatic cancer subtype classification starting from the single-cell transcriptomic dataset of patient biopsies ( 7 ). Recently, it has also been shown that with transfer learning, we can use the knowledge of sensitive drugs for each cell line to predict the patient's treatment once the patient’s cells were confidently mapped on the reference atlas ( 78 ). Here, we demonstrated our method has high accuracy in cell mapping even when we profile cells’ transcriptomes after several culture passages in a different batch or with a different sequencing technique.…”
Section: Discussionmentioning
confidence: 99%
“…For example, we have already shown that we can use breast cancer cell lines for automatic cancer subtype classification starting from the single cell transcriptomic dataset of patient biopsies (7). Recently, it has also been shown that with transfer learning, we can use the knowledge of sensitive drugs for each cell line to predict the patient's treatment once the patient's cells were confidently mapped on the reference atlas (73). Here, we demonstrated our method has high accuracy in cell mapping even when we profile cells' transcriptomes after several culture passages in a different batch or with a different sequencing technique.…”
Section: Discussionmentioning
confidence: 99%
“…Algorithms for efficient use of reference atlases are known as single-cell reference mapping methods [19][20][21], which build upon data integration algorithms to rapidly update an existing reference atlas by integrating a new query dataset. Transferring information from the reference atlas to the query enables efficient cell-type annotation of the query cells, automatic identification of novel (sub) populations [20,22] and unseen disease or treatment affected cells [4,22,23].…”
Section: Introductionmentioning
confidence: 99%